2006
DOI: 10.1021/es0615829
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved Complex Mixtures of Aromatic Hydrocarbons:  Thousands of Overlooked Persistent, Bioaccumulative, and Toxic Contaminants in Mussels

Abstract: Comprehensive two-dimensional gas chromatography-time-of-flight-mass-spectrometry can be used to resolve and identify individual petroleum-derived hydrocarbons in unresolved complex mixtures (UCMs), such as those accumulated by mussels (Mytilus edulis). Mussels exhibiting a range of scope for growth values were collected from sites around the UK coast. Tissue extracts from mussels exhibiting impaired health contained large amounts of aromatic hydrocarbon UCMs compared to the extracts from healthy mussels. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
145
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(157 citation statements)
references
References 25 publications
10
145
0
2
Order By: Relevance
“…This current PAH content is 40x greater than thresholds thought to be associated with the incidence of biological effects (Long et al, 1995), assuming that the biological response for parent and alkylated PAHs is the same. Furthermore, the PAHs found in these sediments are characteristic of PAHs shown to chronically persist within bivalve tissues (Boehm and Quinn, 1977;Stegeman 1981;Farrington et al, 1982;Booth et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…This current PAH content is 40x greater than thresholds thought to be associated with the incidence of biological effects (Long et al, 1995), assuming that the biological response for parent and alkylated PAHs is the same. Furthermore, the PAHs found in these sediments are characteristic of PAHs shown to chronically persist within bivalve tissues (Boehm and Quinn, 1977;Stegeman 1981;Farrington et al, 1982;Booth et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Naturally occurring biological and physical processes, such as volatilization, leaching, and microbial degradation, selectively change the composition of petroleum hydrocarbon compounds, thereby altering the toxicity of contaminated soils to biota [12]. Over time, as the chemistry of petroleum hydrocarbons in the soil changes, soils are left contaminated with what is referred to as an unresolved complex mixture of hydrocarbons (UCM; also referred to as recalcitrant petroleum hydrocarbon residuals) that are resilient to degradation [13,14]. In cold regions, these natural processes take extended periods of time, but can be enhanced through remediation practices.…”
Section: Introductionmentioning
confidence: 99%
“…Although the UCM or "humps" of petroleum hydrocarbons were commonly encountered during GC analysis, little consideration has been given to their toxicological effects [14,15]. Recent studies, however, have showed that the UCM constituents in sediment not only accumulated in benthic organisms, but also caused sub-lethal effects to these organisms [7][8][9][10][11]15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, have showed that the UCM constituents in sediment not only accumulated in benthic organisms, but also caused sub-lethal effects to these organisms [7][8][9][10][11]15]. For example, UCM contributed to the overall toxic effects of oils to the marine amphipod Corophium volutator and its contribution was separate from the PAHs [7].…”
Section: Introductionmentioning
confidence: 99%